Study on Ecological Protection and Restoration : from the Perspective of a New Public Governance Model - WU, Yiming; Zhonghua, Wang; Zijun, He (Advances in Social Sciences Research Journal, 2021)
With the increasingly serious environmental pollution, the sustainable development of human society has become the focus in China and even the world, which makes the theoretical research on environmental governance become particularly important. According to the change process of environmental governance theories, a theory can solve or explain some problems in reality, but with the development and change of economy and society, the theory needs to be innovated and integrated continuously to achieve good environmental governance and continuous improvement. This paper firstly sorts out the historical context and evolution logic of environmental governance theories in China and abroad, and scientifically divides and reviews the development of the theories. Secondly, this paper researches on China’s first batch of ecological protection and restoration pilot projects of MRFFLG in Ganzhou city through various kinds of sources of data collection ,such as semi-structured interviews, field visits and second-hand data collection. It is found that environmental governance changes from operational applied governance to exploring a new paradigm of multi-subjects governance. Moreover, the environmental governance theory is integrated and innovated from several dimensions, such as governance objectives, policies and methods. This paper also puts forward the multiple approaches of environmental governance, and analyzes and solves problems with the multiple logic of environmental governance, and sums up the experience and lessons of environmental governance practice. Finally, this paper looks forward to the theoretical development of environmental governance, which has far-reaching significance for how to construct the environmental governance model with Chinese characteristics and effectively promote the sustainable development of the environment.